Perbandingan Pembangunan Berkelanjutan antara Skema Hutan Kemasyarakatan dan Hutan Desa dalam Meningkatkan Kesejahteraan Masyarakat di Kabupaten Lampung Selatan - Aziz, Fatoni; Tresiana, Novita (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2025)
This study aims to compare sustainable development between members of forest farmer groups under the Community Forestry (Hutan Kemasyarakatan/HKm) and Village Forest (Hutan Desa/HD) schemes in enhancing community welfare in South Lampung Regency. Employing a quantitative approach with a comparative method, the study involved 73 respondents, consisting of 40 members from KTH Rangai Sejahtera (HKm scheme) and 33 members from LPHD Way Kalam (HD scheme), selected through simple random sampling. The research variable focuses on sustainable development, measured using the Sustainable Livelihoods Framework (SLF). Data were analyzed using the non-parametric Mann-Whitney U-Test, which revealed a statistically significant difference in sustainable development outcomes between the two forestry schemes in terms of their contribution to community welfare. KTH Rangai Sejahtera is characterized by nutmeg (Myristica fragrans) as its primary commodity, cultivated extensively across most managed lands and processed into various derivative products. In contrast, LPHD Way Kalam demonstrates strengths in social management and community-based ecotourism, particularly through the utilization of natural attractions such as the Way Kalam Waterfall.